1971
DOI: 10.1287/trsc.5.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Center Location in Simple Networks

Abstract: The general problem is that of locating a central facility in a network so as to minimize the sum of its distances from the sources of flow to it, each distance being appropriately weighted to reflect the associated flow volume and/or cost. In this paper, simple one-pass solution algorithms are given for two classes of topologically simple networks, namely those which are either acyclic or contain exactly one cycle. The first algorithm is based on a reduction procedure that may also yield useful simplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(150 citation statements)
references
References 1 publication
0
148
0
2
Order By: Relevance
“…This problem is called the 1-median problem on a tree. Goldman [25] showed that the problem can be solved in O(n) time, where n is the number of nodes in the tree: Begin with any tip node of the tree. If the demand at that node is equal to or greater than half the total demand of all nodes, the optimal location is at that node.…”
Section: A Taxonomy Of Location Modelsmentioning
confidence: 99%
“…This problem is called the 1-median problem on a tree. Goldman [25] showed that the problem can be solved in O(n) time, where n is the number of nodes in the tree: Begin with any tip node of the tree. If the demand at that node is equal to or greater than half the total demand of all nodes, the optimal location is at that node.…”
Section: A Taxonomy Of Location Modelsmentioning
confidence: 99%
“…, n (cf. Goldman [8]). In case of the unweighted 1-center problem, it is easy to see that the above optimality criterion is equivalent to the so-called midpoint property, i.e., the 1-center lies on the midpoint of a longest path.…”
Section: Convex Ordered Median Problems On Treesmentioning
confidence: 99%
“…[GOLD71] gave an O(n), a linear time, algorithm for solving 1-median problem on a tree. [KARI79] provided an O(n 2 k 2 ) algorithm for finding k medians on a tree with n nodes.…”
Section: 313mentioning
confidence: 99%